THE IMPORTANCE OF EXPATRIATE TRAINING FOR LIVING AND WORKING ABROAD - Stanulović, Milana Z (International Journal of Economic Practice and Policy, 2018)
The specificity of business activity of international companies is, among others, the need for relocating employees for the sake of finishing work assignments in foreign subsidiaries. Having in mind that the host country culture is usually very different than the home country culture, adjustment to a new culture is a slow and step-wise process, which can be facilitated by cross-cultural training. There are multiple methods of cross-cultural training: didactic training, experiential training, attribution training, language training, cultural awareness training, interaction training, cognitive behaviour modification and sequential training. Some of these methods are used more often than others, but complete cross-cultural training implies usage of all these methods for the sake of complete preparation of the expatriate.